Once- versus twice-daily lopinavir/ritonavir tablets in virologically suppressed, HIV-infected, treatment-experienced children: Comparative pharmacokinetics and virological outcome after switching to once-daily lopinavir/ritonavir - Kulkanya Chokephaibulkit (2018)
Objectives: Data on lopinavir/ritonavir tablets administered once daily in children are limited. We compared the pharmacokinetics (PK) of lopinavir/ritonavir twice daily versus once daily in virologically suppressed, HIV-infected children, and assessed the virological outcome, at 48 weeks, in children receiving the regimen of lopinavir/ritonavir once daily. Patients and methods: HIV-infected children receiving a twice-daily lopinavir/ritonavir-based regimen and with an HIV-1 RNA viral load (VL) <40 copies/mL for at least 3 months were enrolled. Intensive steady-state 12 h blood sampling for PK assessment was performed at enrolment. Immediately afterwards, the lopinavir/ritonavir dose was changed to once daily with the equivalent daily dose, and intensive steady-state 24 h blood sampling was repeated 2 weeks later. If the lopinavir Ctroughwas <1.0 μg/mL, the lopinavir/ritonavir dose was increased by 20%-30% and Ctroughmeasurement repeated. CD4 cell counts and VL were determined at baseline and at 12, 24 and 48 weeks. Results: Twelve children were enrolled. The median age was 13.1 years. Lopinavir AUC0-24following twice-daily and once-daily dosing was 169.7 (124.0-200.8) and 167.1 (95.1-228.1) · h/mL, respectively. Seven children, including all six concomitantly receiving efavirenz, had a Ctrough<1.0 μg/mL with once-daily lopinavir/ritonavir dosing, and four of seven children had a Ctrough<1.0 μg/mL after dose adjustment. All children maintained virological suppression throughout the 48 week period. Conclusions: Lopinavir/ritonavir-based once-daily regimens could simplify therapy in children/adolescents with virological control, but a lower lopinavir Ctroughwas evident. Further efficacy studies of lopinavir/ritonavir once daily in children are necessary before routinely recommending this dosing strategy. © The Author 2012. Published by Oxford University Press on behalf of the British Society for Antimicrobial Chemotherapy. All rights reserved.